The relationship between the character of responsibility and academic procrastination in students - Zaimi, Melati; Sukma, Dina (Universitas Negeri Padang, 2023)
Procrastination is a procrastinating behavior in carrying out tasks. Factors causing academic procrastination. If they do not have awareness of the task they have, such as the character of responsibility, students will increasingly procrastinate this behavior. This study aims to analyze: (1) the character of responsibility, (2) students' academic procrastination, and (3) examine the relationship between the character of responsibility and academic procrastination in students and the implications for counseling services. This research method is a quantitative method with a descriptive correlational research type. The study population consisted of 746 students of class X and XI of SMA Negeri 9 Padang with a sample of 260 students selected by Stratified Random Sampling. The instrument used is the